Is education via YouTube effective in increasing compliance with Fe tablet consumption in pregnant women? - Bahar, Hartati; Wahyuni, Mina (Universitas Islam Negeri Alauddin Makassar, 2023)
Anemia is usually considered normal during pregnancy even though it has the potential to be serious and dangerous to the pregnancy because it can cause bleeding, shock, abortion, premature rupture of membranes, and post-partum bleeding. Minimal knowledge about balanced nutrition and foods rich in iron is one of the factors that causes anemia due to lack of nutritional intake. Pregnant women often experience iron deficiency so it is important to consume iron tablets as a substitute for the mother's needs, however, there are many obstacles faced by pregnant women in maintaining compliance with iron tablet consumption. Therefore, it is important to provide education about compliance with iron consumption in pregnant women. The aim of this research is to determine the effectiveness of health education via YouTube regarding compliance with the consumption of Fe tablets among pregnant women at the Jatiraya Health Center and the Perumnas Health Center in Kendari City. This research method is experimental with a pre-experimental study research design with Pretest and Posttest one group design. This design only uses one group, namely the experimental group without a control group. The total sample in this study was 56 people. The sampling technique in this research used the total sampling method. The results of the Paired Samples T Test statistical test showed that there were differences in knowledge (P= 0.000 < 0.05) and actions (P= 0.000 < 0.05) in pregnant women before and after being given the intervention. So it can be concluded that education via YouTube is effective in influencing pregnant women's compliance with consuming Fe tablets.